Differentiation of mixed flower buds in some traditional pear varieties in the region of Skopje - Selamovska, Ana; Miskoska-Milevska, Elizabeta (University of Kragujevac, Faculty of Agronomy, 2018)
The results in the present paper are part of the scientific research project “Autochtonous genetic resources of pears in the Republic of Macedonia”. Flower bud differentiation was examined in five traditional pear varieties (‘Carigradsko Avche’, ‘Letna Kajkushka’, ‘Vodenka’, ‘Zimska Kajkushka’ and ‘Zimnica’) in the region of Skopje. In the region of Skopje, the differentiation of mixed flower buds in the traditional pear varieties starts in summer. The primordia of calyx and corolla are formed in the period from the second half of October to early November. In mid-November, stamen primordia are formed, while in late November the primordia of carpels are formed. In winter months, the archesporial tissue develops and microsporogenesis occurs. In the period from January to March, microgametogenesis and pollen grain development take place. The earliest differentiation of flower buds (approximately 7–10 days) and the earliest blooming (about 3-4 days) are tipical of the variety ‘Carigradsko Avche’, compared to the latest varieties ‘Zimska Kajkushka’ and ‘Zimnica’.
Keywords: differentiation, mixed flower buds, pear, traditional varieties